2018
DOI: 10.1002/jmri.26031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gadolinium‐based MRI contrast agents on liver tissue

Abstract: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2018;47:1367-1374.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…[ 29 ] Mercantepe and coworkers reported in their study that linear or macrocyclic GBCAs had similar toxicity effects on liver tissue as a result of administration. [ 9 ] In this study, we observed that the effects of linear or macrocyclic GBCAs on lung tissue were similar.…”
Section: Discussionsupporting
confidence: 53%
“…[ 29 ] Mercantepe and coworkers reported in their study that linear or macrocyclic GBCAs had similar toxicity effects on liver tissue as a result of administration. [ 9 ] In this study, we observed that the effects of linear or macrocyclic GBCAs on lung tissue were similar.…”
Section: Discussionsupporting
confidence: 53%
“…The most frequent side effects were found as anaphylactoid/hypersensitivity reactions, headache, nausea, dizziness, injection site reactions, feeling www.nature.com/scientificreports www.nature.com/scientificreports/ hot, vomiting and dysgeusia 24 . In an animal model, Gd-based contrast agents were shown to induce necrosis and apoptosis in liver 25 .…”
Section: Discussionmentioning
confidence: 99%
“…[29,59,[61][62][63] While the mechanism has not been unequivocally proven, the presence of Gadolinium deposits suggests that the GCCA release toxic, free Gadolinium most likely from acidic lysosomal compartments within the Kupffer cells. [111][112][113] While nanocrystals are also taken up by Kupffer cells in the liver, the remarkable chemical stability of these materials, even under mildly acidic conditions, should limit the release of free Gadolinium and reduce the likelihood of this particular toxicity mechanism (Figures S9 and S10, Supporting Information).…”
Section: Detecting Nonalcoholic Fatty Liver Disease With Gadolinium Oxide Nanoplatesmentioning
confidence: 99%